Exchange rate misalignment, oil prices and macroeconomic condition in Nigeria - Emmanuel Ayeni; Obaika M. Ohikhuare; Kayode Muhammed Ibrahim; Olatunde wright (Social Sciences and Humanities Open, 2025)
Exchange misalignment remains a significant discussion in international trade and finance due to implications on global capital movement, goods, and services. The exchange rate remains the country's competitive advantage in international trade, which means countries either adopt overvaluation or undervaluation of their domestic currency in line with their productive capacity and volume of interaction with the global world. This study examines the impact of oil prices and macroeconomic conditions on exchange rate misalignment in Nigeria. Findings from the study show that crude oil revenue does not impact exchange rate misalignment. Still, macroeconomic variables such as money supply, degree of openness, external debt, and net foreign assets contribute to the undervaluation of domestic currency. The real interest rate contributed to the overvaluation of domestic currency, probably due to increased foreign portfolio investment during higher interest rates. The study concluded that the domestic currency had been overvalued over the period adopted in this study. The study concluded that there is a need to build a medium-run framework that would reposition spending of crude oil revenue into more productive activities to reduce importation. This will thereby improve the value of domestic currency and the competitive advantage of the currency globally.